Time Synchronization Using Distributed Observer Algorithm With Sliding Mode Control For Wireless Sensor Network - Yew, Tze Hui (2015)

(untitled)
This research describes a novel distributed observer algorithm which uses augmented sliding mode control element to compensate for clock skew for wireless sensor network (WSN), in the world of Internet of Things (IoT). The algorithm is known as Time Synchronization using Distributed Observer algorithm with Sliding mode control element (TSDOS).The main purpose of proposing TSDOS is to estimate a common global clock time by which all nodes within the WSN can use it for communication purpose. Without a common global clock time, it is impossible for the nodes to exchange information since the time reference is different. By using only the local information, TDOS will be able to estimate the skew rate, the offset and the relative skew rate of the perceived virtual clock of the neighboring nodes. TSDOS is designed to be able to adapt to dynamic condition with faster convergence speed and reduced synchronization error. TSDOS has the characteristics of being totally distributed, asynchronous, scalable across different network topological structures and adaptable to ad-hoc nodes deployment and link failures.In this dissertation, TSDOS has been implemented in several experimental simulations subject to different network topology and ad-hoc nodes deployment in MATLAB. The purpose is to observe the performance of TSDOS in terms of synchronization speed and clock error of each individual node in the WSN through the simulation results. Last but not least, a comparison is made between TSDOS and another fully distributed consensus based protocol, Average Time Sync (ATS), and TSDOS proves itself to achieve faster convergence speed and reduced synchronization error induced in the network through MATLAB simulations.